Satisfaction and Barriers of Surgical Safety Checklist Implementation in a Nonmandatory Adoption Resource-Limited Country. Issue 8 (December 2021) - Kasatpibal, Nongyao; Sirakamon, Somjai; Punjasawadwong, Yodying; Chitreecheur, Jittaporn; Chotirosniramit, Narain; Pakvipas, Parichat; Whitney, JoAnne D.
Abstract : Objectives: A surgical safety checklist has been a globally implemented and mandated adoption in several countries. However, its use is not mandatory in Thailand. This study aimed to evaluate the perceptions of surgical personnel on surgical complications and safety and to examine the satisfaction and barriers of surgical safety checklist implementation. Methods: A survey study was performed between November 2013 and February 2015 in 61 Thai hospitals. A questionnaire capturing demographics, perceptions related to surgical complications and safety, and the satisfaction and barriers of surgical safety checklist implementation was distributed to surgical personnel. Results: A total of 2024 surgical personnel were recruited. Nearly all of them reported experience or knowledge of an adverse surgical event (99.6%). Most thought that it could be preventable (98.2%) and quality care improvement could help reduce the occurrence of adverse events (97.7%). Overall, respondents reported a high level of satisfaction with the checklist (mean [SD] = 3.79 [0.71]). The three areas of highest satisfaction were benefit to the patient (mean [SD] = 4.11 [0.69]), benefit to the organization (mean [SD] = 4.05 [0.68]), and reduction in adverse events (mean [SD] = 4.02 [0.69]). Overall, the barrier for implementation of the checklist was rated as moderate (mean [SD] = 2.52 [0.99]). However, the means of barriers in each period, sign in, time out, and sign out, were rated as low (means [SD] = 2.41 [1.07], 2.50 [1.03], and 2.34 [1.01], respectively). Conclusions: The data document that the satisfaction with the checklist are fairly high. However, some barriers were identified. Efforts to increase understanding through more rigorous policy enforcement and strategic support may lead to improving the checklist implementation.